2003
DOI: 10.4161/cbt.2.2.280
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Glycine Inhibits Angiogenesis During Wound Healing and Tumor Growth

Abstract: In this study we investigated the effects of glycine on angiogenesis during embryogenesis, wound healing and tumor growth. In chorioallantoic membrane (CAM) assay, glycine (100 µM) inhibited angiogenesis by more than 50%. We studied dietary glycine's effect on fibrin induced wound healing response in a novel (Fibrin Z-chamber) assay. Fibrin within the chamber triggers the healing cascade leading to formation of granulation tissue (GT) rich in blood vessels and stroma. GT was reduced by more than 30% (p < 0.000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 34 publications
2
22
0
1
Order By: Relevance
“…Glycine treatment was shown to inhibit HUVEC growth and suppress both migration and capillary formation after VEGF stimulation in vitro. These findings strongly support glycine's role as direct inhibitor of angiogenesis and are consistent with previously reported findings on the migration and proliferation of bovine endothelial cells (Amin et al 2003). This was reproducible with endothelial cell stimulation using conditioned medium which was collected from human colorectal cancer cells that are known to overexpress VEGF (Fig.…”
Section: Control Glysupporting
confidence: 91%
See 3 more Smart Citations
“…Glycine treatment was shown to inhibit HUVEC growth and suppress both migration and capillary formation after VEGF stimulation in vitro. These findings strongly support glycine's role as direct inhibitor of angiogenesis and are consistent with previously reported findings on the migration and proliferation of bovine endothelial cells (Amin et al 2003). This was reproducible with endothelial cell stimulation using conditioned medium which was collected from human colorectal cancer cells that are known to overexpress VEGF (Fig.…”
Section: Control Glysupporting
confidence: 91%
“…Moreover, glycine has been shown to prevent Kupffer-cell-dependent liver injury in models of acute liver injury and in chemotherapy models Mikalauskas et al 2011). The indirect effects of glycine have already been demonstrated in various settings: in hepatocellular carcinoma, glycine down-regulates VEGF expression via GlyR, and both melanoma and mammary tumors have been impacted by the presence of glycine, in vivo (Amin et al 2003;Bruns et al 2014;Rose et al 1999a, b). In our study, we identified a direct anti-angiogenic effect on endothelial cells that was regulated via GlyR.…”
Section: Control Glymentioning
confidence: 94%
See 2 more Smart Citations
“…Glycine infusion at either dose level does not seem to affect rat well-being and, at the lower dose, does not perturb blood counts or electrolyte values. Lower doses may be preferential because rats fed a glycine-rich diet for 5 to 12 days show an inhibition of tumor angiogenesis (14). At this time, it is not known if the i.v.…”
Section: Discussionmentioning
confidence: 99%